The Other Italy : The Literary Canon in Dialect - Haller, Hermann W., 1945- (Book collections on Project MUSE., 1999)
Italy possesses two literary canons, one in the Tuscan language and the other made up of the various dialects of its many regions. The Other Italy presents for the first time an overview of the principal authors and texts of Italy's literary canon in dialect. It highlights the cultivated dialect poetry, drama, and narrative prose since the codification of the Tuscan literary language in the early sixteenth century, when writing in dialect became a deliberate and conscious alternative to the official literary standard. The book offers a panorama of the literary dialects of Italy over five centuries and across the country's regions, shedding light on a profoundly plurilingual and polycentric civilization. As a guide to reading and research, it provides a compendium of literary sources in dialect, arranged by region and accompanied by syntheses of regional traditions with selected textual illustrations. A work of extraordinary importance, The Other Italy was awarded the Modern Language Association of America's Aldo and Jean Scaglione Publication Award for a Manuscript in Italian Literary Studies. It will serve scholars as an indispensable resource book for years to come.